The winds of change climate, weather, and the destruction of civilizations - Linden, Eugene (Simon & Schuster Paperbacks, 2007)
Climate has been humanity's constant, if moody, companion. At times benefactor or tormentor, climate nurtured the first stirrings of civilization and then repeatedly visited ruin on empires and peoples. Environmental journalist Linden reveals a recurring pattern in which civilizations become prosperous and complacent during good weather, only to collapse when climate changes--either through its direct effects, such as floods or drought, or indirect consequences, such as disease, blight, and civil disorder. The science of climate change is still young, but the evidence mounts that climate loomed over the fate of societies from arctic Greenland to the Fertile Crescent and from the lost cities of the Mayans in Central America to the rain forests of Central Africa. The tragedy of New Orleans is but the latest instance in which a region prepared for weather disasters experienced in the past finds itself helpless when nature ups the ante--Publisher's description.